Higher education, new challenges and emerging roles for human and social development. (Basingstoke, Hampshire [England] ; New York, N.Y., 2008)
This annual report explores in depth the key issues facing Higher Education institutions in the Twenty-first century including perspectives from the five continents, with special emphasis on the theme of the social commitment of universities. It includes papers from eminent scholars, a Delphi poll from over 70 key experts/practitioners on the subject of creating a knowledge society, and extensive supporting statistics and analytical maps. Its publication coincides with the annual International Barcelona Conference on Higher Education
Keywords: Education, higher,Universties and colleges,Education, humanistic,Education and globalization; Social aspects,Social aspects